2017
DOI: 10.2214/ajr.16.16700
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Safety and Cost Implications of Pediatric Contrast-Enhanced Ultrasound at a Single Center

Abstract: Pediatric CEUS is a safe and potentially cost-effective imaging modality. Using it allows reduction in the ionizing radiation associated with CT and in the gadolinium contrast administration, sedation, and anesthesia sometimes required for MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 25 publications
0
66
0
1
Order By: Relevance
“…24 A study based on a single-centre experience showed no immediate adverse reactions in 305 paediatric CEUS examinations and only 2 (0.7%) delayed adverse reactions. 9 In another study examining children with malignancies, only 2 of the 13 children undergoing CEUS complained of minor and self-limiting symptoms. No change attributable to the ultrasonography contrast was detected on neurological, funduscopic examination, electrocardiography and continuous pulse oximetry.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…24 A study based on a single-centre experience showed no immediate adverse reactions in 305 paediatric CEUS examinations and only 2 (0.7%) delayed adverse reactions. 9 In another study examining children with malignancies, only 2 of the 13 children undergoing CEUS complained of minor and self-limiting symptoms. No change attributable to the ultrasonography contrast was detected on neurological, funduscopic examination, electrocardiography and continuous pulse oximetry.…”
Section: Safetymentioning
confidence: 99%
“…use of ultrasonography contrast agents is still "off-label" for the paediatric population in Europe, it has been widely used with documented safety and accuracy. 1,9,10 A recent and important development has been the approval by the Food and Drug Administration of the use of CEUS for liver examination in children in the USA, 11 and this will alter application not only in the USA but also across the world. Ultrasound practitioners should be mindful that many drugs are used "off-label" in children, and this is not prohibited by medical regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound contrast agents have a similar safety profile in children Intravesical and intracavitary administration …”
Section: Quality and Safetymentioning
confidence: 99%
“…Lastly, CEUS could reduce a number of oncologic follow-up examinations with the use of ionizing radiation and/or general anesthesia. In a study in which the authors evaluated the utility of CEUS in children, it was shown that CEUS substantially decreased the need for further evaluation with MRI or CT. 16…”
Section: Figurementioning
confidence: 99%